Malignant Peripheral Nerve Sheath Tumor (MPNST) of the Uterine Cervix – A Systematic Literature Review and New Case Report with Possible New Therapeutic Approaches - He, Wei; Hu, Zhi Min; Yang, Zhi Hui; Wang, Qin; Schwenzer, Thomas Christoph (Geburtshilfe und Frauenheilkunde, 2024)
Malignant schwannomas of the visceral organs are extremely rare. To date, 19 cases of cervical schwannoma have been reported in the literature worldwide. A single case prompted a review of the literature. The differential diagnosis between melanoma and schwannoma is made using the marker HMB-45, which is positive for melanoma and negative for schwannoma. This differentiation allowed us to identify two of the 20 cases that were probably not schwannomas.The prognosis of malignant cervical schwannoma is poor. Approximately half of the cases develop local recurrence or distant metastases within a short time, despite resection in healthy tissue.In one case, gene sequencing revealed a potential treatment approach with the mTOR inhibitor everolimus and trastuzumab. Unfortunately, the potential efficacy of these treatment options could not be tested because the patient was being treated at another hospital at the time of relapse, and they did not use a drug that matched the NGS profile.
Keywords: malignant schwannoma; cervix uteri; therapy; prognosis; schwannoma